C.A.E. study : does culture affect the level of entrepreneurial activity? a cross cultural study between Singapore & New Zealand. - Chua, Kai Xin. (2008)
The objective of this study is to examine the nature of both New Zealand’s and Singapore’s national culture, their effects on the entrepreneurial orientation of the populations and ultimately the effects on the level of entrepreneurial activity in the two countries.